Gp41 inhibitory activity prediction of theaflavin derivatives using ligand/structure-based virtual screening approaches. (April 2019) - Mostashari-Rad, Tahereh; Saghaei, Lotfollah; Fassihi, Afshin
Graphical abstract: Highlights: Theaflavin digallate, a potent HIV-1 inhibitor, was considered as a template for ligand- and structure-based virtual screening approaches. In silico Lipinski's Rule of Five and ADMET calculations, were performed to select the compounds with the best potential drug-like properties. Molecular docking and molecular dynamic simulations were performed to select compounds with the best pharmacodynamic properties. Some hits with possibly good anti-HIV activities and better pharmacokinetic properties than TF3 were identified. The selected compounds have balanced hydophilicity and lipophilicity and probably better gastrointestinal and blood brain barrier absorption. Abstract: Gp41 and its conserved hydrophobic groove on the NHR region is one of the attractive targets in the design of HIV-1 entry inhibitory agents. This hydrophobic pocket is very critical for the progression of HIV and host cell fusion. In this study different ligand-based (structure similarity search) and structure-based (molecular docking and molecular dynamic simulation) methods were performed in a virtual screening procedure to select the best compounds with the most probable HIV-1 gp41 inhibitory activities. In silico pharmacokinetics and ADMET (absorption, distribution, metabolism, excretion and toxicity) properties filtration also was considered to choose the compounds with best drug-like properties. The results of molecular docking and molecular dynamic simulations of the final selected compounds showed suitable stabilities of their complexes with gp41. The final selected hits could have better pharmacokinetics properties than the template compound, theaflavin digallate (TF3 ), a naturally-originated potent gp41 inhibitor.